Hydrodynamic bearings - Bonneau, Dominique, 1948-; Fatu, Aurelian; Souchet, Dominique (London : ISTE, 2014)
This Series provides the necessary elements to the development and validation of numerical prediction models for hydrodynamic bearings. This book describes the rheological models and the equations of lubrication. It also presents the numerical approaches used to solve the above equations by finite differences, finite volumes and finite elements methods.
3.3.3. Discretization of modified Reynolds equation (problem 2).
Includes bibliographical references and index.
Print version record.
Keywords: Fluid-film bearings -- Mathematical models; Lubrication and lubricants; Bearings (Machinery); Bearings (Machinery); Fluid-film bearings -- Mathematical models; Lubrication and lubricants; TECHNOLOGY & ENGINEERING -- Mechanical; Bearings (Machinery); Fluid-film bearings -- Mathematical models; Lubrication and lubricants; Electronic books